Deviations and Good Moral Values in the Novel Pukul Setengah Lima: A Pragmatic Approach - Janah, Gita Amanda Nur; Izzah, Indy Baitul; Agus, Cecep (Universitas Pamulang, 2025)
This study analyzes the moral values both positive and negative depicted through the characters’ actions in the novel “Pukul Setengah Lima” using a pragmatic literary criticism approach. This approach helps researchers interpret the novel’s messages, allowing readers to clearly understand its moral implications. The study employs a qualitative descriptive analysis method, presenting findings through detailed written descriptions. “Pukul Setengah Lima” is a romance novel by the well-known young writer Rintik Sendu. It narrates the love story of a woman and an adult man while exploring various personal and professional conflicts. The novel conveys both commendable moral values that can be applied in real life and negative moral lessons that serve as warnings for readers. Through character analysis, this study identifies negative moral values such as low self-esteem, dishonesty, domestic violence, and betrayal. Conversely, it highlights positive values, including compassion, resilience in facing life’s challenges, and filial piety toward parents. These values are examined through character dialogues and the author's narrative descriptions. This research contributes to a deeper understanding of how literature conveys moral teachings through character interactions and storytelling. Expanding on the pragmatic literary criticism approach with specific examples enhances the clarity of the study’s findings.